A Qualitative Evaluation of Patient-Perceived Benefits and Barriers to Participation in a Telephone Care Management Program. Issue 2 (November 2015) - Jubelt, Lindsay E.; Volpp, Kevin G.; Gatto, Dana E.; Friedman, Joelle Y.; Shea, Judy A.
Purpose: To examine why high-risk individuals targeted for a telephone care management program participated at low rates. Design: Study design consisted of qualitative, semistructured interviews. Setting: The setting was a large national insurer's telephone-based care management program. The program employed registered nurses to provide individually tailored education and counseling about health and health care. Subjects: Study subjects comprised members of a national insurer who were recruited to participate in a care management program but had either dropped out of the program after a short period of initial engagement or had never participated despite recruitment efforts. Measures: Interview content was divided into four categories: knowledge of the case management program, barriers to program participation, perceptions of benefits of the program, and suggestions for program improvement. Analysis: Investigators conducted a directed content analysis. Results: The most commonly cited barriers to participation were a lack of perceived need and a sense of distrust toward the program and its staff. The most commonly cited benefits were psychosocial support and goal setting. Conclusion: Care management programs may benefit from changes to how insurance plan members are selected for the program and from adjusting program content to address perceived needs among members.